“KEGAGALAN NEGARA” DALAM MENANGGULANGI TERORISME ATAU “NEGARA GAGAL” DALAM MENANGGULANGI TERORISME - Minardi (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2021)
The failure of the de-radicalization program in prisons is evidenced by the high recidivation of terrorism convicts who have launched their actions again. This failure was due to the lack of coordination between stakeholders, namely the Director-General of Social Affairs (Dirjenpas) and the BNPT. Government Science sees that there have been sectoral egos between institutions. This study aims to examine the implementation of deradicalization in prisons and to skin sectoral egos in its implementation. This research methodology uses qualitative descriptive, namely the translation through words, by conducting interviews from September to October 2020. The results show that there is a reluctance of the Director-General of Social Affairs to use the concept of deradicalization and prefers to use the concept of guidance owned by the Director-General of Social Affairs itself. This reluctance was based on the negative stigma of using deradicalization and the feeling that BNPT had never coordinated to coordinate deradicalization. The sectoral ego is the result of not being carefully defined by radicalism and terrorism. Each state institution and the general public have their own definitions, resulting in differences in concept resulting in differences in program design and implementation.